Analysis and simulation of an Adefovir anti‐hepatitis B virus infection therapy immune model with alanine aminotransferase. Issue 5 (1st October 2013) - Su, Yongmei; Zhao, Lei; Min, Lequan
Abstract : Hepatitis B virus (HBV) infection models and anti‐HBV infection therapy models have been set up to understand and explain clinical phenomena. Many of these models have been proposed based on Zeuzem et al. and Nowak et al. 's basic virus infection model (BVIM). Some references have pointed out that the basic infection reproductive number of the BVIM is biologically questionable and gave the modified models with standard mass action incidences. This study describes one anti‐HBV therapy immune model with alanine aminotransferase (ALT) based on standard mass action incidences. There are two basic infection reproductive numbers R 0 and R 1 in the model. It is proved that if R 0 < 1 and R 1 < 1, the disease free equilibrium is locally and globally asymptotically stable, respectively. For the endemic equilibrium, simulation shows that if R 1 > 1, it may be also globally asymptotically stable. Simulations based on clinical data of HBV DNA and ALT can explain some clinical phenomena. Simulations of the correlation between liver cells, HBV DNA, cytotoxic T lymphocytes and ALT are also given.